ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DALAM MENGHADAPI PESAING di PT. SEMEN INDONESIA - Fatun; Nurul Ulfa; Nurul Hayati; Putri Ayu Wulandari; Alviatun Nurul Hidayah; Siti Muhassinah; Sofiyah; Yuhan Atiqah Wardah (ICO EDUSHA, 2022)
The purpose of this research to determine the application of good corporate governance in facing competition at PT Semen Indonesia, a company engaged in the cement sector. The type of research used is observation and interviews. The research method used is a qualitative method with interactive data analysis. The results of this study found that PT Semen Indonesia with the application of the principles of good corporate governance namely: transparency, accountability, responsibility, independence and fairness was able to compete even though there were many new players in the field of development, by always trying to create new innovations, and providing products and services that were quality according to the needs of customers and society in general, and digitizing the production process, by providing convenience for customers with digital marketing initiatives through the SobatBangung platform, AccessToko and Online Official Store. . Keywords: GCG, Competitor, PT. Semen Indonesia   References   https://radarkudus.jawapos.com/ekonomi/02/03/2022/skor-penilaian-gcg-semen-gresik-terkualifikasi-sangat-baik/   Kunaifi, A. (2016). Manajemen Pemasaran Syari’ah Pendekatan Human Spirit; Konsep, Etika, Strategi, dan Implementasi (1 ed., Vol. 1). Maghza Pustaka. Kunaifi, A. (2017). Peran Strategis Pedidikan Islam Dalam Mewujudkan Islamic Good Governance. FIKROTUNA, 4(2). https://doi.org/10.32806/jf.v4i2.2749 Negara, P.B.U.M. (2002). Keputusan Menteri Badan Usaha Milik Negara Nomor: KEP-117/M-MBU/2002 Tentang Penerapan Praktek Good Corporate Governance. Jakarta (ID). Kemen BUMN.   Pahlevi, M., & Mawardi, M. K. (2016). Penerapan Prinsip Good Corporate Governance (Gcg) Pada Bumn Berorientasi Global (Studi Kasus pada PT. Semen Indonesia (Persero) Tbk. dalam Mengelola Thang Long Cement Joint Stock Company). Brawijaya University.   Patrice, G. J. (2016). Analisis Penerapan Prinsip-prinsip Good Corporate Governance pada PT Aroset Jatra Karindo. Agora, 4(2), 273-279.   Surat Keputusan Direksi PT. Semen Indonesia (Persero) Tbk, Nomor: 022.1/kpts/Dir/2016   Strengthening Capabilities To Sustain Growth PT Semen Indonesia (Persero) Tbk Laporan Tahunan 2021 Annual Repor   Yohanmar, T. Y. (2016). Analisis Penerapan Good Corporate Governance Pada PT Sumber Jaya Gemilang. Agora, 4(2), 222-228.